2018
DOI: 10.29264/jinv.v13i1.2490
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh investasi dan tenaga kerja serta pengeluaran pemerintah terhadap pertumbuhan ekonomi serta kesempatan kerja

Abstract: AbstrakPenelitian ini bertujuan untuk menganalisis dan mengetahui pengaruh efek langsung dan tidak langsung investasi dan tenaga kerja dan pengeluaran pemerintah terhadap pertumbuhan ekonomi dan kesempatan kerja di Malinau. Studi tersebut menemukan bahwa: tenaga kerja secara signifikan mempengaruhi pertumbuhan ekonomi, sementara investasi dan belanja pemerintah tidak berpengaruh signifikan terhadap pertumbuhan ekonomi. Buruh dan mengupayakan pertumbuhan ekonomi yang signifikan pada pekerjaan, investasi dan bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 0 publications
1
7
0
12
Order By: Relevance
“…The results of this study agree with research by Priambodo (2015) which states that labor has a positive and significant effect in districts/cities in Central Java Province. Hellen et al, (2018) also found significant influence between labor variables on economic growth, a significance test which showed less than α = 0,05, indicating that the large number of labor absorbed and worked was able to encourage or increase economic growth in Malinau District. Konyongian et al (2019) argue that labor has a positive and significant effect on economic growth in each study.…”
Section: Discussionmentioning
confidence: 93%
“…The results of this study agree with research by Priambodo (2015) which states that labor has a positive and significant effect in districts/cities in Central Java Province. Hellen et al, (2018) also found significant influence between labor variables on economic growth, a significance test which showed less than α = 0,05, indicating that the large number of labor absorbed and worked was able to encourage or increase economic growth in Malinau District. Konyongian et al (2019) argue that labor has a positive and significant effect on economic growth in each study.…”
Section: Discussionmentioning
confidence: 93%
“…The results of research conducted by Dimas and Woyanti found that investment has a negative relationship with employment in DKI Jakarta [9]. The same thing can also be seen from the results of research which states that direct investment has no significant effect on job opportunities in Malinau Regency [10].…”
Section: Introductionmentioning
confidence: 81%
“…Karena SDM merupakan orang yang bergerak atau menggunakan skillnya dalam menciptakan barang dan jasa (Hellen et al, 2018). Hubungan tenaga kerja dengan pertumbuhan ekonomi dijelasakan oleh Robert Solow dari MIT dan Trevor Swan dari Australian National University secara sendiri-sendiri mengembangkan model pertumbuhan ekonomi yang sekarang sering disebut dengan nama model pertumbuhan Neo-Klasik.…”
Section: Konsep Collaborative Governanceunclassified